Stratospheric ozone in boreal fire plumes – the 2013 smoke season over central Europe - Trickl, T.; Vogelmann, H.; Flentje, H.; Ries, L. (Atmospheric Chemistry and Physics, 2015)
In July 2013 very strong boreal fire plumes were observed at the northern rim of the Alps by lidar and ceilometer measurements of aerosol, ozone and water vapour for about 3 weeks. In addition, some of the lower-tropospheric components of these layers were analysed at the Global Atmosphere Watch laboratory at the Schneefernerhaus high-altitude research station (2650 m a.s.l., located a few hundred metres south-west of the Zugspitze summit). The high amount of particles confirms our hypothesis that fires in the Arctic regions of North America lead to much stronger signatures in the central European atmosphere than the multitude of fires in the USA. This has been ascribed to the prevailing anticyclonic advection pattern during favourable periods and subsidence, in contrast to warm-conveyor-belt export, rainout and dilution frequently found for lower latitudes. A high number of the pronounced aerosol structures were positively correlated with elevated ozone. Chemical ozone formation in boreal fire plumes is known to be rather limited. Indeed, these air masses could be attributed to stratospheric air intrusions descending from remote high-latitude regions, obviously picking up the aerosol on their way across Canada. In one case, subsidence from the stratosphere over Siberia over as many as 15–20 days without increase in humidity was observed although a significant amount of Canadian smoke was trapped. These coherent air streams lead to rather straight and rapid transport of the particles to Europe.